Building an inpatient addiction medicine consult service in Sudbury, Canada: preliminary data and lessons learned in the era of COVID-19 - Tara Leary; Natalie Aubin; David C. Marsh; Michael Roach; Paola Nikodem; Joseph M. Caswell; Bridget Irwin; Emma Pillsworth; Maureen Mclelland; Brad Long; Sastry Bhagavatula; Joseph K Eibl; et al. (BMC, 2023)
Abstract Objective The goal of this study was to (1) Describe the patient population of a newly implemented addiction medicine consult service (AMCS); (2) Evaluate referrals to community-based addiction support services and acute health service use, over time; (3) Provide lessons learned. Methods A retrospective observational analysis was conducted at Health Sciences North in Sudbury, Ontario, Canada, with a newly implemented AMCS from November 2018 and July 2021. Data were collected using the hospital's electronic medical records. The outcomes measured included the number of emergency department visits, inpatient admissions, and re-visits over time. An interrupted time-series analysis was performed to measure the effect of AMCS implementation on acute health service use at Health Sciences North. Results A total of 833 unique patients were assessed through the AMCS. A total of 1,294 referrals were made to community-based addiction support services, with the highest proportion of referrals between August and October 2020. The post-intervention trend for ED visits, ED re-visits, ED length of stay, inpatient visits, re-visits, and inpatient length of stay did not significantly differ from the pre-intervention period. Conclusion Implementation of an AMCS provides a focused service for patients using with substance use disorders. The service resulted in a high referral rate to community-based addiction support services and limited changes in health service usage.